PWE-016 Evolution of endotherapy for high grade dysplasia and early cancer in Barrett's oesophagus: completing the audit cycle in a single centre. (28th May 2012) - Usman-Saeed, M; Gowland, K; Carr, C; Buchanan, J; Mahmood, S; Smart, H L
Abstract : Introduction: We have previously reported our outcomes for endotherapy in Barrett's oesophagus (BO) patients with high grade dysplasia (HGD) and intra-mucosal adenocarcinoma (IMAC) to this Society. Using Endoscopic Mucosal Resection (EMR) and Argon Plasma Coagulation (APC) in patients unfit for surgery, no procedure related mortality, minimal morbidity but a recurrence rate of 27% was seen. 1 We were interested to complete the audit cycle, particularly with the advent of Radiofrequency Ablation (RFA), which has become available since our initial report. Methods: The aim was to re-audit the outcomes of endotherapy for HGD and IMAC in patients with BO attending our gastroenterology unit and to compare the results to our previous audit in terms of outcome and complications. A retrospective review of patient records using specialised endoscopy and patahology databases was performed. Demographic information, diagnosis, procedural details and subsequent progress was entered into a Microsoft Access database and analysed using Microsoft Excel. Results: A total of 54 patients who underwent endotherapy from January 2005 to December 2011 were identified. The mean age of the group was 71 (range 45–89) years. There were 42 males and 12 females. The underlying diagnosis was HGD in 49 and IMAC in 5. Patients with focal raised lesions were treated by EMR, while diffuse dysplasia was treated by mucosal ablation (APC or RFA). Eight patients had EMR alone. EMR was followed by APC in six patients and RFA in 20. Five patients had EMR, APC and RFA. Ten patients had RFA and five APC alone. Six patients (11%) developed an oesophageal stricture requiring dilatation. No bleeding, perforation or procedure related mortality occurred. Over a median follow-up of 18.9 months (range 0–71), two patients (4%) developed a recurrence of their condition, defined as the reappearance of HGD or IMAC after one or more negative biopsies. Two patients (4%) had persistent disease. These four patients (7%) were referred for surgery and underwent oesophagectomy. Seven patients are still under treatment with RFA, 38 have no dysplasia, four low grade dysplasia with one lost to follow-up. During the follow-up period three patients have died, one in the post-operative period. Conclusion: In our department, endotherapy has evolved with APC being replaced by RFA, often in combination with EMR. This has resulted in a considerable improvement in patient outcomes (7 vs 27% recurrence/persistent disease), no procedure related mortality and minimal morbidity. Endotherapy is now used as the primary treatment for HGD and IMAC with surgery being reserved as a salvage procedure if no response or disease recurs. Competing interests: None declared. Reference: 1. Duffy U, et al. Gut 2009;58 (Suppl 1):A146.